Potency of Stichopus hermanii extract as oral candidiasis treatment on epithelial rat tongue - Syamsulina Revianti; Kristanti Parisihni (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Oral candidiasis is the most prominent oral fungal infection with Candida albicans (C. albicans) as 75% of ethiologic factor. Golden sea cucumbers (Stichopus hermanii) have been consumed by Asian community as folk medicine. It has been known to have antifungal and immunomodulator agent thus potential to be explored as treatment in oral candidiasis. Purpose: The aim of this study was to examine the potency of Stichopus hermanii extract as oral candidiasis treatment. Method: The study was an experimental laboratories research with post test only control group design. Thirty male wistar rats were divided into 5 groups i.e negative control, positive control and 3 treatment groups. Oral candidiasis condition were induced by spraying C. albicans suspension on dorsal tongue of wistar rats, once in 2 days for 14 days. The treatment groups were given Stichopus hermanii extract on the dose of 4.25 ml/kgBW, 8.5 ml/kgBW, 17 ml/kgBW once daily for 14 days. The expression of anti C. albicans antibody and TNF-α were examined by immunohistochemistry on ephitelial tongue. Data was analyzed by Manova and LSD test. Result: Anti C. albicans antibody expression were higher in positive control group than in negative control group while TNF-α expression were lower in positive control group than in negative control group (p<0.05). Treatment with Stichopus hermanii extract on all doses decreased the expression of anti C. albicans antibody and increased the expression of TNF-α (p<0.05). Conclusion: Stichopus hermanii extract decreased the expression of anti C. albicans antibody and increased the expression of TNF-α in epithelial rat tongue.